Breakthrough Cancer Pain: The Current Pharmacological Management - Mochamat Mochamat; Taufik Eko Nugroho; Satrio Adi Wicaksono (JAI (Jurnal Anestesiologi Indonesia), 2022)
Background: Breakthrough pain (BTP) is a transient increase in pain that occurs on a background of stable pain. It contributes substantially to the suffering experienced by most cancer patients. The pharmacologic options for management of BTP have been expanded considerably in the past decade. Opioids remain the most effective pharmaceuticals used for the BTP case. In this systematic review we attempted to provide the currently available clinical data about pharmacological treatment for breakthrough cancer pain.Objective: To evaluate the efficacy of pharmacological treatments for Breakthrough painMethods: We searched the Cochrane Central Register of Controlled Trials (CENTRAL) and PubMed for the last ten years (from September 2010 to September 2020. Further potentially relevant studies were identified from reference lists of studies marked for inclusion and relevant reviews. Two review authors independently assessed trial quality and extracted data. We screened the search results and included studies if they met the selection criteria.Result: We screened 205 publications of which 14 met the inclusion criteria. In total, we analysed data from 2129 participants. Overall, participant with BTP were treated with short acting opioid. Literature searching did not find any published evidence of non opioid drug to treat the BTP. Most adverse effects of the investigated drugs seemed to be moderate.Conclusion: The findings of this review suggest that rapid onset opioids play significant role for BTP. Future studies may be conducted to explore the efficacy and safety profiles each regimen for patients with certain categories of cancer.